2018
DOI: 10.1093/jb/mvy030
|View full text |Cite
|
Sign up to set email alerts
|

Rim domain loops of staphylococcal β-pore forming bi-component toxin S-components recognize target human erythrocytes in a coordinated manner

Abstract: Staphylococcus aureus bi-component pore-forming toxins consist of S- and F-components, and form hetero-octameric beta-barrel pores on target blood cell membranes. Among them, γ-haemolysin (Hlg2 and F-component of Luk (LukF)) and LukED (LukE and LukD) possess haemolytic activity, whereas the Panton-Valentine leukocidin (LukS-PV and LukF-PV) does not lyse human erythrocytes. Here, we focussed on four loop structures in the rim domain of S-component, namely loops -1, -2, -3 and -4, and found that replacement of L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 28 publications
2
21
0
Order By: Relevance
“…S1A). Loop 1 of LukE contributed to hemolysis, but more minimally than the larger DR1 (16). Of note, Peng et.…”
Section: Role Of Loops 1 and 4 Within The Rim Domain In Luke Mediatedmentioning
confidence: 91%
See 3 more Smart Citations
“…S1A). Loop 1 of LukE contributed to hemolysis, but more minimally than the larger DR1 (16). Of note, Peng et.…”
Section: Role Of Loops 1 and 4 Within The Rim Domain In Luke Mediatedmentioning
confidence: 91%
“…As LukD and HlgB are critical for targeting erythrocytes (16,20,22), and S and F subunits can form active pores in non-canonical pairs (29,30), we next combined the gain of function chimeras with LukD and HlgB. Remarkably, we found that LukS E-DR1 exhibited full hemolytic activity when combined with LukD or HlgB, indistinguishable from WT LukED (Fig.…”
Section: Determination Of the Critical Regions Of Luke For Hemolysismentioning
confidence: 93%
See 2 more Smart Citations
“…Conversely, the loop structures in the rim domain of S-components have been investigated as candidate factor(s) that interact with target cell, because S-components lack the PC-binding site. Four loop structures have different amino acid sequences in the rim domain of Hlg2 and LukE, and these loops are involved in erythrocyte binding (Figure 1(a) and Figure S1) [8]. Hlg2 and LukE have been suggested to recognize the same receptor on the human erythrocytes via a different site of Duffy Antigen Receptor for Chemokines (DARC) [9].…”
mentioning
confidence: 99%